A solvent extraction-based procedure for removal of 46Sc impurity from reactor produced [45Ca]CaCl2 for its potential use in bone pain palliation. (October 2022) - Chakravarty, Rubel; Ram, Ramu; Patra, Sourav; Sarma, Haladhar Dev; Chakraborty, Sudipta
Abstract: Calcium-45 [T½  = 163 d, Eβ (max) = 0.3 MeV] is a pure β − emitting radioisotope which can be envisaged for potential use in palliative care of pain due to skeletal metastases of primary cancer. During production of 45 Ca in nuclear reactor via 44 Ca (n, γ) 45 Ca route, 46 Sc is co-produced as a radionuclidic impurity. In this study, we have optimized a single-step solvent extraction procedure for complete removal of 46 Sc impurity from [ 45 Ca]CaCl2 . The purified radiotracer was administered intravenously in normal Wistar rats and preferential bone uptake could be demonstrated by ex vivo biodistribution studies. Highlights: A solvent extraction procedure was optimized for removal of 46 Sc from [ 45 Ca]CaCl2 . The purified [ 45 Ca]CaCl2 showed high uptake in hydroxyapatite. Biodistribution studies in Wistar rats showed preferential skeletal uptake.